Nutritional value of the leaves and stalks of sorghum genotypes of bmr mutant and normal - Aguilar, Poliana Batista de; Assis Pires, Daniel Ananias de; Santos Rodrigues, Jose Avelino; Reis, Sidnei Tavares dos; Rocha Junior, Vicente Ribeiro; Moncao, Flavio Pinto [UNESP]; Tolentino, Daniela Cangussu; Barros Frota, Benara Carla (Univ Fed Grande Dourados, 2015)
This study aimed to evaluate the nutritional value of the leaves and stalks of sorghum genotypes of mutant and normal BMR used for cutting and grazing. Twenty sorghum genotypes were used, there being eleven mutants BMR and nine normal. The design was a randomized block with 3 replications, where each genotype was a treatment (20 treatments) totaling 60 experimental plots. The nutritional value was analyzed after 42 days of regrowth after the first cut, determine the content of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF). Regarding PB of leaves and stems was no difference between genotypes. The average levels ranged from 18.31 to 21.14 % CP leaves for BR 800 and BR001AXTX2784bmr respectively. The mean levels of the stems ranged from 6.98 to 14.33 % CP for CMSXS205AxTX2785bmr and BR007AxTX2785bmr. In DM, NDF and ADF of leaves and stems compared there was no difference between genotypes. The maturity affects the nutritional value of sorghum genotypes of mutant and normal BMR is recommended to use them for cutting and / or grazing around 42 days after planting or regrowt.
Keywords: forage; isogenic; mutation; brown midrib